The relationship between total quality management and firm performance at Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam , Selangor Darul Ehsan / Nurul Hazirah Zainol - Zainol, Nurul Hazirah (2017)
This study investigates the relationship between Total Quality Management and firm performance at Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam Selangor. The data collected through questionnaires that has been distributed to the total sample size of 210 employees at Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam, Selangor. The objectives of this study were to identified the most contributing factor of Total Quality Management towards firm performance and to examined the relationship between Total Quality Management and firm performance at Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam, Selangor. Besides, this study also provided benefits to the researcher and the employee in the organization as it gains more understanding and knowledge about Total Quality Management elements studied this research which are training, customer focus and leadership within the organization. Once they get to know which elements of Total Quality Management that applied the most in their organization, the top management is able to increase the element’s approach that can lead to higher reputation of the organization. Findings of this study concludes that leadership is the most contributing factor in Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam, Selangor with the highest mean of 4.1114 and standard deviation .49684 compared to other factors, training with mean 4.0657 and standard deviation .46305; and customer focus with mean 4.0762 and standard deviation .52306. Meanwhile, there was a strong, positive relationship between Total Quality Management and firm performance at Pejabat Setiausaha Kerajaan Negeri Selangor, Shah Alam, Selangor with correlation value (r=.706, n=210, p<.01)